SIFAT KIMIA BATANG KELAPA SAWIT (Elaeis guinensis Jacq) BERDASARKAN LETAK KETINGGIAN DAN KEDALAMAN BATANG Chemical Properties of Oil Palm Trunk (Elaeis guinensis Jacq) Based on Height and Depth of Trunk - Hermawan, Asep; Diba, Farah; Mariani, Yeni; Setyawati, Dina; haida, Nur (Universitas Tanjungpura, 2014)
Research aimed to measure the chemical compound in oil palm stem (Elaeis guinensis Jacq) based on height (base, middle, top) and depth (side, medium and core). Chemical properties studied are hot water soluble extractives content, solubility in 1% NaOH, benzene-soluble alcohol, holocellulosa, alpha - cellulose and lignin content. The procedure based on ASTM D 1110 – 56. Result of research showed that the average value of the levels of extractive substances in hot water ranged from 11,963% -15.032%, the average value of extractive substances soluble in 1% NaOH was range from 16.639% -18.027% and the average value of the levels extractive soluble substances of alcohol benzene ranged from 8.552% -10.693%. Meanwhile the average of holocellulose levels ranged from 82.534% -88.328% and the average value of alpha cellulose content ranged from 11.243% -68.761%. The average value of the lignin content ranges between 6.213% -33.702%. Analysis of variance showed that height and depth of stem was not significance to the levels of extractive substances in hot water, extractive substances soluble in 1% NaOH, extractive soluble substances of alcohol benzene, and holocellulose content. Meanwhile for alpha cellulose was significant. The height of stem was highly significant effect to lignin content, meanwhile depth of stem was not significant. This result showed that stem of oil palm can be used for composite board, particle board and other wood product. Keywords: Oil palm stem, extractives, lignin, cellulose, stem height, stem depth